Legal principles of countermeasures against violations of customs rules by the State Customs Service of Ukraine - Yu. V. Bukharieva (Bulletin of Kharkiv National University of Internal Affairs)
The article emphasizes that Ukraine really has a carefully developed system of legal acts aimed at preventing and countering violations of customs rules. This includes constitutional norms, international agreements and domestic legislation aimed at ensuring effective customs activities and combating illegal customs activities.